Improving the Methodology for Teaching Handball Elements to Schoolchildren (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is written to improve the methodology of teaching handball elements to schoolchildren. The article examines the results of scientific research from handball players on ways to correctly select exercises in the development of general and physical fitness.